2015
DOI: 10.1111/1365-2745.12409
|View full text |Cite
|
Sign up to set email alerts
|

C:N:P stoichiometry of Artemisia species and close relatives across northern China: unravelling effects of climate, soil and taxonomy

Abstract: Summary1. Carbon (C), nitrogen (N) and phosphorus (P) stoichiometries play critical roles in the function and structure of ecosystems by affecting important ecological processes. Yet, most studies to date have concentrated on foliar stoichiometry of phylogenetically distantly related species.2. Here, we hypothesized that (i) plant stoichiometry of closely related species still shows biogeographic patterns because of the geographic patterns of abiotic environment at the regional scale and (ii) even related spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 81 publications
7
65
1
Order By: Relevance
“…This was probably because the main source of P is rock weathering, which is a long process (Shen et al 2011) and not significantly influenced by grazing. A negative correlation between TC and BD (P = 0.037, Table 2) was found in this study, like some others (Steffens et al 2008;Yang et al 2015). This could be due to the fact that BD depends on the size and density of soil mineral and organic particles and how they are packed together (Mora and Lázaro 2014); therefore, low BD is a remarkable feature of soil organic matter immobilization (Yang et al 2015).…”
Section: X) and The Vegetation Characteristics (Y)supporting
confidence: 60%
See 1 more Smart Citation
“…This was probably because the main source of P is rock weathering, which is a long process (Shen et al 2011) and not significantly influenced by grazing. A negative correlation between TC and BD (P = 0.037, Table 2) was found in this study, like some others (Steffens et al 2008;Yang et al 2015). This could be due to the fact that BD depends on the size and density of soil mineral and organic particles and how they are packed together (Mora and Lázaro 2014); therefore, low BD is a remarkable feature of soil organic matter immobilization (Yang et al 2015).…”
Section: X) and The Vegetation Characteristics (Y)supporting
confidence: 60%
“…The variation in pH in this study is probably related to vegetation coverage, variations of root systems, and organic matter content (Su et al 2005). The BD is an important factor affecting key soil functions including soil water, nutrients, and carbon stocks (Mora and Lázaro 2014) and therefore is an indicator of soil porosity versus compaction (Yang et al 2015). Our experiment showed significantly increased BD in plots of higher grazing intensities (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies found that leaf stoichiometry is impacted strongly by genetics, for example life form, family, genus, species (Kerkhoff et al 2006;Li et al 2011;Yang et al 2015), and provenance or genotype (Å gren and Weih 2012; Wu et al 2014). However, we found that the effect of provenance (genetics) on leaf stoichiometry was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Plant stoichiometry is strongly impacted by taxonomic affiliation (genetics) (Wright et al 2005;Demars and Edwards 2008;Zhang et al 2012;Yang et al 2015) and environment, such as soil nutrients (Ordonez et al 2009;Chen et al 2013) and climate (Reich and Oleksyn 2004;Elser et al 2010;Yuan et al 2011;Dijkstra et al 2012). How genetics and the environment affect plant stoichiometry has recently attracted a great deal of attention from ecologists (Ordonez et al 2009;Han et al 2011;Å gren and Weih 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These trends help to explain why the numerical values of the N vs. P scaling exponent decline from the tropics to higher latitudes for each of the major plant functional groups. Species composition and soil relative nutrient availability are additional factors that are related to variation of the N vs. P scaling exponent across different ecoregions (continents) because they influence the N and P stoichiometry [48]. For example, herbs and conifers are especially well represented in North America and Europe compared to the other four continents, whereas broad-leaved deciduous species dominate the species composition in Asia, and evergreen broad-leaved species dominate Oceania, Africa and South America (Fig.…”
Section: Possible Mechanisms Of the Different N-p Scaling Exponentsmentioning
confidence: 99%